Response of organic and inorganic sources of nitrogen on tomato production in Parwanipur, Bara, Nepal - Chaudhary, Jeet Narayan; Srivastava, Arvind; Sharma, Moha Dutta; Gautam, Ishwori Prasad (Journal of Agriculture and Natural Resources, 2024)
An experiment was conducted to study the response of nitrogen (N) on tomato production using randomized completely block design (RCBD) design with two factorial arrangements of treatments in three replications at the research field of Directorate of Agricultural Research (DoAR), Parwanipur, Bara, Nepal in the winter seasons of 2020/21 and 2021/22. Factor A consisted of three genotypes (AVTO 1409, and AVTO 1306 and check Pusa Ruby). Factor B was comprised with five combinations of N application (i.e. 4 applications of N 100 and 50% of the recommended dose of fertilizers (RDF) through farm yard manure (FYM) and poultry manure (PM) with one control only RDF (200:150:120 kg N:P2O5:K2O + 10 t ha-1 FYM). RDF of P2O5 and K2O were applied equally in all treatment combinations. The plot was maintained at 9 m2 (3 m x 3 m) and 28-day-old seedlings were transplanted at a 75 cm x 60 cm distance between rows and plants. The analysis of results observed highly significant variation for yield. However, their interaction effect was found non-significant. Whereas, Genotypes AVTO 1409 produced the highest plant height (71.20 cm,) and the earliest flowering (52 days). The earliest harvest (86 days) was found in AVTO 1306 along with the highest fruit weight. (47.9 g); fruit length (5.84 cm), fruit diameter (6.41 cm.), and the higher marketable yield (40.21 t/ha) followed by genotype AVTO 1409 (38.77 t/ha). The lowest yield (25.63 t ha-1) was found in Pusa Ruby over the years. Likewise, the combined application of 50 % N from PM and 50% from inorganic fertilizer produced the highest plant height (74.20 cm) which was statistically at par with the control, the earliest harvest (89 days), diameter (5.92 cm) and length (5.98 cm) and average weight (41.6 g) of fruits and marketable yield (39.36 t/ha) while the supply of 100 % N only from FYM produced the lowest yield (31.21 t/ha) in the mean over the combined years. Based on the results, genotype AVTO 1306 and the application of 50% N from PM and 50% from inorganic sources were found promising in the sustainable production of tomato.